Postawy nauczycieli wobec edukacji informatycznej i medialnej w szkole - Bałażak, Marta (Wydawnictwo Uniwersytetu Rzeszowskiego, 2018)
Edukacja informatyczna i medialna we współczesnej szkole już stała się faktem, ale nie każdy nauczyciel jest równie zainteresowany wykorzystaniem jej w swojej pracy. Sposób i poziom wykorzystania najnowszych osiągnięć technologii w edukacji wskazuje na różne postawy nauczycieli wobec ich pracy.

The informatics and media education in modern school already has become a fact, but not every teacher is equally interested in using it in their work. The way and level of using the newest achievements of technology in education indicates different attitudes of teachers towards their job.
Teacher’s attitudes towards informatic and media education at school
Keywords: nauczyciel; technologia informacyjna i medialna; praca nauczyciela; postawa wobec pracy; teacher; computer and media technology; teacher’s work; teatcher’s attitudes towards work